Hubungan antara Peran Individu, Iklim Organisasi, dan Tuntutan Pekerjaan dengan Stres Kerja pada Guru Sekolah Luar Biasa (SLB) Negeri Pembina Kota Kupang - Yusuf Monito Kana Lede; Agus Setyobudi; Christina Rony Nayoan; Luh Putu Ruliati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Work stress does not appear suddenly, but is influenced by three main factors, namely individual factors, organizational factors (including individual roles and job demands), and environmental factors such as organizational climate. Stress in SLB teachers has a broad impact, both on teachers, students, and school institutions. The impacts include psychological and physical disorders, decreased performance, and serious health problems if not treated. This study was conducted at SLB Negeri Pembina Kupang City which has diverse student characteristics, such as blind, deaf, mentally retarded, physically disabled, and autism. This condition makes teachers face different challenges compared to teachers in other SLBs, so this study is considered relevant. The purpose of this study was to determine the factors related to work stress in SLB teachers. The study used an analytical observational approach with a cross-sectional design, implemented in May 2025. Data were collected through questionnaires from 35 teachers selected by simple random sampling from a total of 55 teachers. Data analysis was carried out using the chi-square test with a significance level of 0.005. The results show that individual roles have a significant relationship with work stress (p = 0.003), job demands are also significant (p = 0.002), and organizational climate is significantly related to work stress (p = 0.002).